USE OF CUCURBITACEOUS BUSH AS SUPPORT MATERIAL IN ANAEROBIC FIXED BED REACTOR - Magassy, T. B.; Fagundes, J. V. C.; Araújo, A. S.; de Oliveira Netto, A. P. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The project evaluated the performance of a continuous domestic sewage treatment system. The work is distinguished by using the cucurbitaceous vegetable bush as support material, little studied for this purpose of biological treatment. This material is characterized by being light, cheap and easily found in the region of study, besides being natural and with characteristics favorable to the biomass immobilization. The cucurbitaceous bush has been shown very efficient for the treatment of effluents, relating the concepts of sustainability and efficiency. An anaerobic fixed bed reactor, in bench scale, with continuous stream flow rate was used. The system performance was evaluated in three different hydraulic retention times (HRT), 8, 6 and 4 hours. The mean effluent values for ammoniacal nitrogen were 22.71 mg N / L; 27.97 mg N / L; and 32.40 mg N / L for hydraulic retention times (HRT), 8, 6 and 4 hours, respectively. In terms of organic matter removal represented by COD, the reactor had an average efficiency of 73.0%, 59.7% and 64.0% for each time studied. In this research was developed a stable, reliable and efficient sewage treatment system, based on the principles of biological treatment.